Cobalt-Catalyzed Carbonylation of C(sp2)–H Bonds with Azodicarboxylate as the Carbonyl Source - Ni, Jiabin; Li, Jie; Fan, Zhoulong; Zhang, Ao (Organic letters, 2016)
A novel and efficient approach for the C(sp2)–H bond carbonylation of benzamides has been developed using stable and inexpensive Co(OAc)2·4H2O as the catalyst and the commercially available and easily handling azodicarboxylates as the nontoxic carbonyl source. A broad range of substrates bearing diverse functional groups were tolerated. This is the first example where cobalt-catalyzed C(sp2)–H bond carbonylation occurs with azodicarboxylate as the carbonyl source.